Orthodontic Protocol Using Mini-Implant for Class II Treatment in Patient with Special Needs - Fernando Pedrin Carvalho Ferreira; Anderson Paulo Barbosa Lima; Eliana de Cássia Molina de Paula; Ana Claudia de Castro Ferreira Conti; Danilo Pinelli Valarelli; Renata Rodrigues de Almeida-Pedrin (Hindawi Limited, 2016)
Improving facial and dental appearance and social interaction are the main factors for special needs (SN) patients to seek orthodontic treatment. The cooperation of SN patients and their parents is crucial for treatment success. Objective. To show through a case report the satisfactory results, both functional and esthetic, in patients with intellectual disability, congenital nystagmus, and severe scoliosis. Materials Used. Pendulum device with mini-implants as anchorage unit. Results. Improvement of facial and dental esthetics, correction of Class II malocclusion, and no root resorption shown in the radiographic follow-up. Conclusion. Knowing the limitations of SN patients, having a trained team, motivating and counting on the cooperation of parents and patients, and employing quick and low-cost orthodontic therapy have been shown to be the essential factors for treatment success.